2018
DOI: 10.1002/ffj.3470
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in essential oils and selected fragrance extracts. Some examples. A review

Abstract: The use of essential oils (EOs) worldwide continues to rise, and EOs are already established in folk and western medicine as remedies against inflammation, respiratory diseases, and infections, and are used for aromatherapy, insect repellents, food preservatives, and in the perfume and cosmetics industries. Pesticide residues are already present in the environment, however, and are thus also found in the aromatic plants used for EO production. The control of pesticides in EOs is therefore essential, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For instance, in the EU, the European Food Safety Authority (EFSA) requires the analysis of insecticides such as dimethoate, deltamethrin, and imidacloprid in olive oil [52]. Reviews by Tascone et al [13] and Nikolic et al [53] discussed pesticide residues in natural cosmetic ingredients (extracts, absolutes, and essential oils) and attributed the sources of contamination to raw materials and environmental conditions (soil, rainfall, and processing equipment). A synthesis of over 225,000 datasets of pesticides in essential oils revealed that cold-pressed oils have a higher probability of pesticide contamination than distilled oils [54].…”
Section: Chemical Contaminants Associated With Natural Cosmetic Ingre...mentioning
confidence: 99%
“…For instance, in the EU, the European Food Safety Authority (EFSA) requires the analysis of insecticides such as dimethoate, deltamethrin, and imidacloprid in olive oil [52]. Reviews by Tascone et al [13] and Nikolic et al [53] discussed pesticide residues in natural cosmetic ingredients (extracts, absolutes, and essential oils) and attributed the sources of contamination to raw materials and environmental conditions (soil, rainfall, and processing equipment). A synthesis of over 225,000 datasets of pesticides in essential oils revealed that cold-pressed oils have a higher probability of pesticide contamination than distilled oils [54].…”
Section: Chemical Contaminants Associated With Natural Cosmetic Ingre...mentioning
confidence: 99%
“…Organophosphorus and organochlorine pesticide residues were found in citrus EOs, especially those produced by cold-pressing and conventional agriculture practice, albeit with a concentration lower than 1 mg L −1 . Tebuconazole and propiconazole co-distillated in peppermint EO with a different degree depending on the vapour pressure [ 289 ]. Cymoxanyl, dimethoate, and tebuconazole residues exceeded the maximum residue level set by the European Union in thyme samples from Poland [ 288 ].…”
Section: Regulation and Safety Issues Of Plant Extractsmentioning
confidence: 99%
“…These volatiles are the mixtures of several compounds, which are divided mainly in two groups of terpenes (by the coupling of isoprene units) and aromatics (derived from phenylpropane) constituents (Bakkali et al, 2008, Bajpai & Baek, 2016. Along with widely applications of essential oils in the pharmaceutical and perfume industries (Che & Zhang, 2019), their potential in the management of major agricultural pests has also been demonstrated in the recent years (Nikolic et al, 2018, Singh & Pandey, 2018, Gaire et al, 2019.…”
Section: Introductionmentioning
confidence: 99%